Selection methods and heterogenous population effects in genetic oat breeding - Viau, Luiz Volney Mattos; Carvalho, Fernando I. F. de (Pesquisa Agropecuaria Brasileira, 2014)
The effects of selection methods and genetic variability were studied through the genetic grain yield potential and other important agronomic traits in oat populations. The experiments were carried out in the 1984 and 1985 seasons at the Experimental Station of the Federal University of Rio Grande do Sul (EEA/UFRGS) at Guaíba, RS, Brazil. Among selection methods, the pedigree (P2) and mixture (M1 2) were the most efficient identifier of superior grain yield genotypes, when compared to populational and massal methods. Analysis of other traits like number of panicle/m2, grains/panicle, grain weight, plant stature, resistance to lodging, heading-time and harvest index helped to identify the populations with best performance. Finally, differences among selection methods only were observed when the genetic variability was high and also it was the most important aspect for identifying superior genotypes on the basis of quantitative traits.